Blood-cerebrospinal fluid (CSF) barrier dysfunction means reduced CSF flow not barrier leakage - conclusions from CSF protein data - Hansotto REIBER (Arquivos de Neuro-Psiquiatria)
ABSTRACT Background: Increased concentrations of serum proteins in cerebrospinal fluid (CSF) are interpreted as blood-CSF barrier dysfunction. Frequently used interpretations such as barrier leakage, disruption or breakdown contradict CSF protein data, which suggest a reduced CSF flow rate as the cause. Results: Even the severest barrier dysfunctions do not change the molecular size-dependent selectivity or the interindividual variation of the protein transfer across barriers. Serum protein concentrations in lumbar CSF increase with hyperbolic functions, but the levels of proteins that do not pass the barrier remain constant (brain proteins) or increase linearly (leptomeningal proteins). All CSF protein dynamics above and below a lumbar blockade can also be explained, independent of their barrier passage, by a reduced caudally directed flow. Local accumulation of gadolinium in multiple sclerosis (MS) is now understood as due to reduced bulk flow elimination by interstitial fluid (ISF). Nonlinear change of the steady state in barrier dysfunction and along normal rostro-caudal gradients supports the diffusion/flow model and contradicts obstructions of diffusion pathways. Regardless of the cause of the disease, pathophysiological flow blockages are found in bacterial meningitis, leukemia, meningeal carcinomatosis, Guillain-Barré syndrome, MS and experimental allergic encephalomyelitis. In humans, the fortyfold higher albumin concentrations in early fetal development decrease later with maturation of the arachnoid villi, i.e., with beginning CSF outflow, which contradicts a relevant outflow to the lymphatic system. Respiration- and heartbeat-dependent oscillations do not disturb net direction of CSF flow. Conclusion: Blood-CSF and blood-brain barrier dysfunctions are an expression of reduced CSF or ISF flow rate.